Knowledge, Attitude, Beliefs, and Practice Related to Concussion Injury Among Sports Physical Therapists in Riyadh, Saudi Arabia. A Cross-sectional Analysis - Ahmed M. Almansour; Mohammed A. Alamri; Naif Z. Alrashdi; Mohammad Miraj (Wolters Kluwer Medknow Publications, 2024)
Background and Objective: Sport-related concussions (SRC) are estimated to affect more than 55 million individuals annually. Physical therapists ought to have fundamental knowledge regarding the evaluation and treatment of SRC. Thus, this study aims to evaluate the knowledge, attitude, and practice of the physical therapists regarding SRC management in Riyadh, Saudi Arabia. Materials and Methods: The cross-sectional study enrolled 83 sports physical therapist who had atleast undergraduate degree and above in physical therapy from Riyadh region. The participants who worked outside the Riyadh region were excluded. A validated adopted questionnaire was used to evaluate the outcome measures. Results: The study showed that sport physical therapists have a good understanding and knowledge about concussions having 3.91 ± 0.98 scores on the five-point Likert scale. In addition, participants were able to recognize concussion signs and symptoms correctly; however, they felt that they lacked confidence to make a decision regarding return to play. Conclusion: Our study revealed important knowledge gaps regarding the utilization of concussion severity scales, management of youth concussion, and/or the use of neurological imaging modalities for diagnosing concussion cases.